Population Perception of Bathing and Virus Outbreaks in Baixada Santista in the 2025 season - Moraes , Nauana Cristina de (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This study analyzes the perception of residents and tourists in Baixada Santista regarding water quality and virus outbreaks in the region, particularly during the 2025 summer season. The research focuses on the impacts of increased tourism on basic sanitation systems and the spread of waterborne and foodborne diseases, as well as the relationship between sanitation infrastructure and public health security. Methodology – Field research was conducted from January 13 to 16, 2025, involving 252 participants, including residents and tourists, in the municipalities of Santos, Praia Grande, São Vicente, and Guarujá. Questionnaires were applied to assess perceptions of water quality, concerns about viruses, and the influence of sanitation infrastructure on public health. The data were supplemented with institutional analyses from sources such as CETESB and the Ministry of Health. Originality/relevance – The study fills a gap by integrating population perception of water quality and virus outbreaks with sanitation infrastructure. The research highlights the importance of environmental education as a fundamental strategy to raise awareness about the risks associated with water contamination and the need to adopt proper sanitary practices. Results – The analysis revealed that 35% of respondents do not feel insecure about virus outbreaks and water quality, and only 58% acknowledge that sanitation infrastructure directly affects their health. Although environmental monitoring indicates areas with poor water quality, many respondents consider this situation "common" during the high season, downplaying health risks. Theoretical/methodological contributions – The study contributes to the debate on sanitation and public health by using an integrated approach that combines social perception with technical data. The results indicate the need for educational campaigns and more effective public policies to reinforce awareness of the impacts of sanitation infrastructure on water quality and collective health. Social and environmental contributions – The study highlights the importance of institutional mobilization to promote access to information on water quality and health risks, emphasizing the need for investments in sanitation and environmental education. The adoption of preventive measures, coupled with greater public engagement, can reduce virus outbreaks and improve the bathing water quality of Baixada Santista’s beaches.